Systematic approach and strategies for building information modelling (BIM) adoption in the Jordanian construction industry - Al-Diabat Al-Btoush, Mohammad (2018)
Many countries consider the construction industry as one of the most challenging industries. The major problems facing construction companies and have ardently caused its low performance improvements over the years cannot be overemphasized. Among others, the causes include poor communications and exceptional fragmented environment relating to the construction sector. The Jordanian construction industry is a very crucial segment of Jordan’s economy. In 2014, it contributed about 5.8% to the gross domestic product (GDP) of Jordan, which is more than the agricultural, electricity and water sectors. However, the construction industry in Jordan faces low productivity issue which is obviously due to repeated delays in the construction project besides cost overrun. On the other hand, many studies on the adoption of building information modelling (BIM) have been conducted in various countries including Norway, Finland, Sweden, Germany, Malaysia, Singapore, France, USA, Australia, and UK where BIM has proven the capabilities to develop information integration, business process flow, productivity, and reduce complexities, uncertainties, conflicts, and fragmentations, among others. BIM is the latest development which is a promising, an evolving procedural and technological shift within the AEC sector. This research is aimed to provide support development in the Jordanian construction industry practice by developing a BIM adoption framework. The contractors, owners and consultants can use this framework to assess and comprehend how ready they are for BIM adoption. To meet this aim, related literature was comprehensively elaborated in two contexts. The first context was the Jordan construction industry in order to explore the current criteria for construction practice and spot-related challenges. The second context was BIM technology, the concept, practice, development, adoption condition, and best practices to select the theoretical framework for BIM adoption from the best practices list. To conceptualize the selected theoretical adoption framework, the research followed a qualitative approach and 15 semi-structured interviews were conducted with the leading construction organizations in the Jordanian construction industry. Three levels of validity and reliability checks were performed; the first level was a focus group workshop where the researcher discussed the results with four construction experts who suggested some adjustments regarding the drivers’ components in the theoretical framework, followed by the second level of validity where 228 questionnaires were answered by construction organizations. The results were analyzed using the structured equation modelling technique where one of the hypotheses were rejected and a second adjustment regarding the conceptual framework components took place. The last validity check was done by discussing the conceptual framework with the three major industry players in Jordan i.e. the ministry of public work and housing, the Jordanian construction contractors association and the Jordanian engineers association to generate the finalized adoption framework. Findings revealed that the adoption of BIM among construction organizations in Jordan is still at the pre-BIM stage where it faces barriers and confronts challenges such as, but not restricted to, the lack of BIM awareness, training centers, BIM specialists, government support, and financial resources, and resistance to change. This study proposed a practical conceptual BIM adoption framework validated by the construction industry key players where it is expected to support and accelerate the adoption operation amongst the Jordanian construction industry significantly. Moreover, the proposed adoption framework could be used as a benchmarking tool to measure the organizations’ readiness to adopt BIM technology. It had been observed from previous literatures (and later confirmed by the interviews and questionnaire results) that some of the problems faced by Jordanian construction industry are: poor design, poor scheduling and planning, change orders, lack of competitive technical staff and ineffective communications among others, leading to issues such as cost and time overruns. Most of the participants approved that the use of ITC on their business increase their efficiency, saving time and decreasing cost. Nonetheless, the finding is different from that of the BIM. Numerous specialists from the construction body are aware of BIM but never applied it in practice. Also, some were familiar of the advantages of BIM, but majority stated they had no knowledge of BIM. In the same way, this study exposed that those experts who knew about BIM were in the age of 30-49. The people of older ages are uninterested in learning a new process. The fresh engineers have no idea about BIM. The research proposed an expository revision that asset the best predictable adoption standards for BIM adoption. The adoption standards would help the firms to recognize the BIM field of capability and assess their present ability to adopt BIM. Moreover, the study supposed to increase the present awareness on BIM by recording concerns associated with BIM adopting from the construction organizations viewpoint. Furthermore, the results concluded in this study could assist the industry sector to realize the BIM adoption problem inside the situation of Jordan. This research supposed to have a significant importance to the construction sector by reason of the absenteeism of a suitable model to adopt BIM in regard of the Jordanian construction background.